Siklus Hidup Organisasi : Suatu Analisis Perkembangan Organisasi (Jurnal Administrasi Bisnis, 2010)
Organization is born from the idea or proposal which is declare by the founder. Intheir way, every organization will experience up and down, stagnant, or even collapse,if planning wasnât implemented and systematic effort. Organization life cycle givesa description and analysis about phase of the organizationâs development, conditioncharacteristics which were encounter in the every development and also implicationswhich were faced in every development phase, also treatment needed to turn backorganization objective.Keywords: organization life cycle, organization development